INTERACTIVE TEACHING METHODS AND THEIR ROLE IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE TO ASTRONAUTS - M L Novikova (Russian Language Studies, 2016)
Aiming at mastering language in the shortest term while using specified language material is the priority in professionally-oriented teaching Russian as a foreign language. It influences the choice of forms and methods of language teaching in the framework of competence approach, including informational, educational, game-based, problematical ones and so on, which helps to implement flexible teaching models. Interactive teaching methods are based on direct interaction of foreign astronauts with their learning environment which dictates the necessity of developing language skills, forming competence to solve communicative tasks in Russian either in a learning or professional environment. Teaching Russian to astronauts takes places in realistic communication simulation during flight preparation or in a space orbit.